3D Coffee‐Ring Effect: The Coffee‐Ring Effect on 3D Patterns: A Simple Approach to Creating Complex Hierarchical Materials (Adv. Mater. Interfaces 16/2019). Issue 16 (23rd August 2019) - Mirbagheri, Marziye; Hwang, Dae Kun
Abstract : In article number1900003 by Marziye Mirbagheri and Dae Kun Hwang, the coffee‐ring effect of a polymer solution on a 3D patterned surface and selective wrinkle formation are described. After evaporation of the polymer solution, the polymer deposits on the microposts and base except around the microposts displaying wrinkle and smooth zones following plasmas treatment.